Photometric redshifts for type Ia supernovae in the supernova legacy survey - Palanque-Delabrouille, N; Ruhlmann-Kleider, V; Pascal, S; Rich, J; Guy, J; Bazin, G; Astier, P; Balland, C; Basa, S; Carlberg, R; Conley, A; Fouchez, D; et al. (2010)
We present a method using the SALT2 light curve fitter to determine the redshift of type Ia supernovae in the Supernova Legacy Survey (SNLS) based on their photometry in g', r', i' and z'. On 289 supernovae of the first three years of SNLS data, we obtain a precision σΔz/(1+z)= 0.022 on average up to a redshift of 1.0, with a higher precision of 0.016 for z < 0.45 and a lower one of 0.025 for z > 0.45. The rate of events with |Δ z|/(1+z) > 0.15 (catastrophic errors) is 1.4%, and reduces to 0.4% when restricting the test sample of spectroscopically confirmed Type Ia supernovae. Both the precision and the rate of catastrophic errors are better than what can be currently obtained using host galaxy photometric redshifts.Photometric redshifts of this precision may be useful for future experiments which aim to discover up to millions of supernovae Ia but without spectroscopy for most of them. © 2010 ESO.